Political Regimes and Currency Crises. (3rd July 2015) - Steinberg, David A.; Koesel, Karrie J.; Thompson, Nicolas W.
<x xml:space="preserve">Abstract</x> This paper examines the relationship between political regime type and currency crises. Some theories suggest that democratic regimes, owing to their greater political transparency and larger number of veto players, should have a lower risk of currency crisis than dictatorships. Alternative arguments emphasize the advantages of political insulation and rulers with long time horizons, and imply that crises should be most likely in democracies and least common in monarchic dictatorships. We evaluate these competing arguments across four types of political regimes using a time‐series cross‐sectional dataset that covers 178 countries between 1973 and 2009. Our findings suggest that the risk of currency crisis is substantially lower in monarchies than in democracies and other types of dictatorship. Further analyses indicate that the adoption of prudent financial policies largely account for this robust negative association between monarchies and the probability of currency crises. This suggests that political regimes strongly influence financial stability, and perverse political incentives help explain why currency crises are so common.